Midwife roles to decline maternal mortality rate - Ambar Dwi Erawati; Rinayati Rinayati; Sri Wahyuning (International Journal of Public Health Science (IJPHS), 2020)
In order to reduce maternal mortality in Central Java, this Province has a superior program which is called 5Ng (Jateng Gayeng Nginceng Wong Meteng/Central Java Glad to See Pregnant Women). Implementation of childbirth assistance in Semarang and Kendal districts in order to reduce maternal mortality has its own model. Based on the preliminary survey, the maternal mortality rate in Semarang and Kendal regencies has decreased. This research aimed to explain the implementation of delivery assistance by midwives in the framework of accelerating reduction in maternal mortality. This study used a qualitative approach with descriptive analytical specifications. Research subjects were midwives in Semarang and Kendal Regencies. Data collection method was conducted by direct in-depth interview. Normal childbirth assistance in Semarang Regency is carried out at the Midwife Independent Practice, Village midwife practice, at the village public health center and public health center with delivery assistance of at least four hands (two midwives). In Kendal Regency normal delivery assistance is performed at first health facility.